Psychometric properties and Longitudinal Measurement Invariance of the Spanish version of the Alcohol Expectancies Questionnaire Short Form among young adult binge drinkers - González-Ponce, Bella M.; Pilatti, Angelina; Rivarola Montejano, Gabriela; Bravo, Adrián J.; Fernández-Calderón, Fermín (2024)
Fil: González-Ponce, Bella M. University of Huelva. Department of Clinical and Experimental Psychology; Spain.